Effect of Lunasia amara Blanco on Sperm Number, Sperm Motility, and Testicular Histology of Male Rats - Muhammad Ja’far Luthfi (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2015)
Sanrego (Lunasia amara), has been used in the folk medicine to increase and/or to treat male fertility. However there is no scientific evidence to confirm the positive effect of the plant on an improvement of male fertility. The objective of this research was to study the effects of the plant (on adult Sprague-Dawley male rats) at the doses of 30 mg/kg, 60 mg/kg, and 90 mg/kg on the sperm count, motility, and testicular histology. Administration were given by force-feeding between 10.00 am and 12.00 pm daily for a period of 42 days followed by sperm quality analysis and testicular histology evaluation. The sperm analysis showed that the sanrego increased the sperm count and sperm motility. The testicular histology also revealed positive effect of the plant on spermatogenesis. Overall the present study showed the sanrego is potential plant to increase male fertility.